Sistem Kepercayaan Sunda Wiwitan Sebagai Wujud Nilai Ketuhanan Dalam Pancasila di Kampung Adat Cireundeu - Salsabila, Alysia Dwi; Qhoirunnisa, Amallia Siti; Asya'bani, Ikhsan Amirulloh; Ajizah, Laisya Nur; Adzila, Sayida Kaila; Fitria, Ratna (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to understand the belief system of Sunda Wiwitan as a manifestation of the values of divinity in Pancasila. This study employs a qualitative method with a case study approach in the Cireundeu Traditional Village, Cimahi City. Data were collected through in-depth interviews with traditional leaders and followers of Sunda Wiwitan, direct observation in Cireundeu Village, and secondary documentation in the form of articles, books, and documentary videos. The analysis was conducted thematically using the interactive model of Miles and Huberman. The results show that Sunda Wiwitan not only teaches personal faith but also instills social and spiritual responsibility that aligns with the first principle of Pancasila. This teaching is practiced not merely as a legacy from ancestors, but as a form of self-awareness of human identity, nature, and the Supreme Being. Its concept of divinity is monotheistic and is embodied through respect, self-control, and the balance of human relations with nature. Practices such as the One Sura Ceremony, Namaan, and Kurasan become part of a way of life that unites spirituality and social ethics through the values of compassion and kindness. To understand the manifestations of these divine values, this research employs a qualitative method with a case study approach.